Dynamic Research EvaluAtion for Management (DREAM) - International Food Policy Research Institute (International Food Policy Research Institute, 2009)
DREAM, or Dynamic Research EvaluAtion for Management, is a menu-driven software package for evaluating the economic impacts of agricultural research and development (R&D). Users can simulate a range of market, technology adoption, research spillover, and trade policy scenarios based on a flexible, multi-market, partial equilibrium model. With DREAM you can define a range of technology investment, development, and adoption scenarios and save them in an integrated database. Scenarios are described using market, R&D, and adoption information for any number of separate “regions.” Some factors, such as taxes, subsidies, growth rates, and price elasticities, can be specified as constant or as changing over the analysis period. Each region in which production takes place may have its own pattern of technology adoption. After specifying the initial conditions for each region, you can simulate the likely effects of technology development and adoption on prices; on quantities produced, consumed, and traded; and on the flow of economic benefits to producers, consumers, and government. DREAM handles simple to relatively complex evaluation problems using a standardized interface. A number of market assumptions are possible: small open economy, closed economy, vertically integrated farm and post-harvest sectors in a single economy, or multiple trading regions. The software also accommodates technology-driven shifts in supply or demand, and users may specify constant or variable shift effects over time in farmers fields. Importantly, DREAM’s multiple region specification can simulate various technology “spillover” scenarios wherein a technology may be adopted in more than one region. Changes in the pattern of technology spillovers can significantly alter the size and distribution of R&D benefits. DREAM has been applied to the evaluation of individual projects in a national context as well as to entire commodity sectors at a subcontinental or continental scale. And while it was designed primarily to evaluate options for R&D that is yet to be undertaken (ex ante assessments), DREAM has also been successfully applied to analyzing the effect of past research (ex post assessments).